The compact Hα emitting regions of the Herbig Ae/Be stars HD 179218 and HD 141569 from CHARA spectro-interferometry. Issue 2 (3rd October 2016) - Mendigutía, I.; Oudmaijer, R. D.; Mourard, D.; Muzerolle, J.
Abstract: This work presents CHARA/VEGA Hα spectro-interferometry ( R ∼ 6000, and λ/2B ∼ 1 mas) of HD 179218 and HD 141569, doubling the sample of Herbig Ae/Be (HAeBe) stars for which this type of observations is available so far. The observed Hα emission is spatially unresolved, indicating that the size of the Hα emitting region is smaller than ∼0.21 and 0.12 au for HD 179218 and HD 141529 (∼15 and 16 R *, respectively). This is smaller than for the two other HAeBes previously observed with the same instrumentation. Two different scenarios have been explored in order to explain the compact line emitting regions. A hot, several thousand K, blackbody disc is consistent with the observations of HD 179218 and HD 141569. Magnetospheric accretion (MA) is able to reproduce the bulk of the Hα emission shown by HD 179218, confirming previous estimates from MA shock modelling with a mass accretion rate of 10 −8 M⊙ yr −1, and an inclination to the line of sight between 30$^°$ and 50$^°$ . The Hα profile of HD 141569 cannot be fitted from MA due to the high rotational velocity of this object. Putting the CHARA sample together, a variety of scenarios is required to explain the Hα emission in HAeBe stars – compact or extended, discs, accretion, and winds – in agreement with previous Brγ spectro-interferometric observations.